Evaluation of the crop water stress index (CWSI) in chili pepper (Capsicum) under drip irrigation in the arid conditions of the north coast of Peru - Duran, M. (2021)
As irrigation water decreases, crop transpiration also decreases, resulting in an increase in leaf temperature and an increase of the crop water stress index (CWSI). Therefore, in the study, the response of Capsicum to different irrigation regimes was evaluated with periodic measurements of leaf temperature, stomatal conductance and estimation of the CWSI. The treatments consisted of a complete drip irrigation (RO) and deficit irrigation (RD-78 and RD-58) that received 78% and 58% of the complete irrigation, applying a total volume of water of 3363, 2618 and 1956 m3 ha-1 for RO, RD-78 and RD-58, respectively; and obtaining maximum yields of 30.2, 13.9 and 12.9 t ha-1 with CWSI of 0.50, 0.62 and 0.54 in C. bacatum, C. annumm and C. chinense, respectively. The highest stomatal conductance values ​​ranged from 724 to 887 mmol s-1 m-2, with CWSI from 0.1 to 0.3. The CWSI value of 0.3 (soil moisture from 25 to 33%) results in a good indicator of the time of irrigation, and it might be a criterion to be incorporated to save water and improve the management of Capsicum irrigation programs.